Non-compliance with the Constitutional Court's Decision from the Perspective of Constitutional Law : Ketidakpatuhan terhadap PutusanMahkamah Konstitusi dari Perspektif Hukum Tata Negara - Narwoko; Rifqi Ridlo Phahlevy; Abdul Fatah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the forms of non-compliance with the Constitutional Court Decision regarding Manpower and to find a constitutional solution to the problem of non-compliance with the Constitutional Court Decision regarding Manpower.This research is a juridicial normative study using a statutory, case, and conseptual approach.Using legal materials in the form of a Constitutional Court Decision related to Manpower.From the research results, it can be concluded that the Constitutional Court Decision regarding Manpower are not obeyed by the adressats. Various forms of non-compliance with the Constitutional Court Decision regarding Manpower-related Laws were not followed up and partially fulfilled in the form of government policies such as the Regulation of Minister of Manpower, Circular of the Minister of Manpower. Some laws are in the legislative process. The constitutional solution that has the potential to realized for non-compliance with the Constitutional Court Decision is the implementation of the concept of judicial order, judicial defferal, and imposition of sanctions.